MOTIVASI MASYARAKAT DALAM MEMBUDIDAYAKAN AYAM GAOK DI PULAU POTERAN, KABUPATEN SUMENEP, JAWA TIMUR - Wulandari, Anggi Dwi; Zuhriyah, Amanatuz; Widodo, Slamet (Jurnal Ilmu Ilmu Agribisnis: Journal of Agribusiness Science, 2025)
One of the native chicken breeds in Indonesia with the potential for broiler development is the gaok chicken, originating from Poteran Island, Sumenep Regency, East Java. This research aims to understand the motivations of the community in breeding native chickens. The study was conducted in three villages on Poteran Island, Sumenep Regency, namely Palasa Village, Gapurana Village, and Essang Village. The selection of these locations was based on the origin of the native chicken, Poteran Island, which is administratively situated in Talango District, Sumenep Regency, East Java. A sample of 30 respondents was determined using the snowball sampling technique. The research was conducted from September 2023 to February 2024. Data collection was carried out through structured interviews employing a questionnaire. Motivation in this research was assessed through three aspects: existence needs, relatedness needs, and growth needs. Measurement utilized Likert scales and was analyzed descriptively. The study's findings indicate that the level of motivation among the community to breed native chickens mostly falls into the low category. Keywords: existence needs, growth needs, motivation, native chicken, relatedness needs